Non-IgE-reactive allergen peptides deteriorate the skin barrier in house dust mite-sensitized atopic dermatitis patients - Pfisterer, Karin; Wielscher, Matthias; Samardzic, David; Weinzettl, Pauline; Symmank, Dorte; Shaw, Lisa E.; Campana, Raffaela; Huang, Huey-Jy; Farlik, Matthias; Bangert, Christine; Vrtala, Susanne; Valenta, Rudolf; et al. (Frontiers in Cell and Developmental Biology, 2023)
Atopic dermatitis (AD) is a chronic inflammatory skin disease that typically begins during early childhood and frequently persists into adulthood. Characteristic symptoms of AD include itchy, scaly, inflamed skin lesions and a pronounced impairment of the skin's protective epithelial barrier, causing substantial burden for patients. AD is often accompanied by sensitization to allergens, such as house dust mite (HDM). To date, the precise factors that induce acute flares in AD and a possible contribution of HDM allergens are yet not fully understood. Here we show that exposure of AD skin to the HDM allergen Der p 2 can induce inflammatory responses in skin keratinocytes. Interestingly, non-IgE-reactive Der p 2 peptides deteriorate the epidermal barrier function by reducing the expression of barrier genes and by inducing alarmin gene expression. This results in the upregulation of genes associated with epidermal hyperplasia causing significant perturbations in epidermal homeostasis. Our data suggest the involvement of Der p 2 peptides in initiating the transition from a barrier deficiency to a pronounced barrier disruption and may pave the way for new adjuvant therapies in AD.